2010
DOI: 10.1021/je1002913
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Adsorption Properties of Corncob-Derived Activated Carbon with High Surface Area

Abstract: Corncob, a widespread and inexpensive natural resource in China, was used to prepare activated carbon (AC) by chemical activation with potassium hydroxide (KOH). The adsorption equilibrium and kinetics of H2, CH4, and CO2 on AC were investigated at different temperatures. Adsorption isotherms of H2, CH4, and CO2 were correlated with the Langmuir and Freundich equations, and the heat of adsorption was determined. It was revealed that the Freundich adsorption equation was more apt to describe the adsorption proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…The mixture was filtered in a funnel under gravity and once the oil dripping stopped from the filter paper the sample was weighed. The oil adsorption capacity (g/g) was estimated using the following equation : OAC=wwowo where w is the weight of the sample before adsorbing oil and w o is the weight of the sample after adsorbing oil. All measurements were performed in triplicate and average values are reported.…”
Section: Methodsmentioning
confidence: 99%
“…The mixture was filtered in a funnel under gravity and once the oil dripping stopped from the filter paper the sample was weighed. The oil adsorption capacity (g/g) was estimated using the following equation : OAC=wwowo where w is the weight of the sample before adsorbing oil and w o is the weight of the sample after adsorbing oil. All measurements were performed in triplicate and average values are reported.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, a lot of kinetic models are proposed to describe the experimental data. For example, Langmuir model [24,25], Langmuir-Freundlichmodel [26,27], pseudo-first-order [28], pseudo-second-order [29], and Avrami's model [21,30,31]. Kinefuchi et al [30] found that Avrami's fractional-order kinetic model could describe the desorption process well.…”
Section: Desorption Kineticsmentioning
confidence: 99%
“…The correlation coefficients for the Freundlich plot is higher than that for the Langmuir plot, which indicates that the adsorption of wool carpet dyes can better be described by the Freundlich adsorption isotherms. High surface area activated carbons have been used as efficient adsorbents for the removal of organic dyes from water [44][45][46][47][48][49][50]. Inspired by the observed high surface area (2129 m 2 ·g −1 ) and large pore volume (2.69 cm 3 ·g −1 ), we investigated the adsorption properties of wool carpet dyes (LO and LG) on NCM_1_600.…”
Section: Introductionmentioning
confidence: 99%